The Role of Technology and Infrastructure in Improving Operational Efficiency - Muhajji, Muhajji; Rappe, Ambo; Halim, Muh.Rizal; Yunus, Muhammad Yusri (Bata Ilyas Educational Management Review, 2024)
This study examines the role of technology and infrastructure in improving operational efficiency across various industries, highlighting the integration of advanced technologies and robust infrastructure. A mixed-methods approach was employed, combining quantitative data from structured surveys and qualitative insights from semi-structured interviews with key stakeholders across diverse sectors, including manufacturing, banking, and urban development. The data were analyzed using statistical and thematic analysis techniques. The study finds that integrating advanced technologies such as automation, artificial intelligence (AI), and the Internet of Things (IoT), along with robust IT and physical infrastructure, significantly enhances productivity, reduces costs, and fosters innovation. These results align with the dynamic capabilities theory, emphasizing the importance of an organization’s ability to adapt and innovate continuously. However, challenges such as significant upfront investments, technological obsolescence, and the need for continuous employee training were noted. The findings also underscore the necessity of developing generalized models that can be applied across various contexts to enhance the generalizability of results. The study provides actionable insights for practitioners and policymakers on strategic planning and investment in technology and infrastructure. It highlights the importance of balancing short-term efficiency gains with long-term strategic benefits, advocating for continuous employee development and sustainable practices. Future research should focus on longitudinal studies to track these investments' long-term impacts and applicability across diverse organizational contexts.